Simulation of uranium hexafluoride gas flow inside the axisymmetric rotor using OpenFOAM software - V. Ghazanfari; A.A. Salehi; A. Keshtkar; M. H. Askari; M. M. Shadma (مجله علوم و فنون هسته‌ای, 2022)
To increase the performance of a gas centrifuge, it is necessary to stabilize an axial flow inside the rotor. For this purpose, computer simulation is an effective method. In the present work, a specific solver (ICDB) was developed in OpenFOAM to simulate the gas flow in the rotor. Creating a solver is important because OpenFOAM is free and open-source software. According to a study carried out by a research group, high-speed airflow is considered on a flat plate to assess the accuracy of this solver. To validate the ICDB, the results are compared with those of Fluent software and other researchers. It is found that the results corresponding to ICDB solver are in good agreement with other effects. Moreover, using the ICDB solver and the fluent software, the uranium hexafluoride gas flow inside the axisymmetric rotor was simulated considering different drives such as the thermal drive (wall and caps) and the mechanical drive (scoop). The obtained results show that the developed solver in OpenFOAM can simulate the uranium hexafluoride gas flow inside the rotor.